2016
DOI: 10.1002/elan.201501125
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of β‐Cyclodextrin Functionalized Silver Nanoparticles and Reduced Graphene Oxide Composite for the Determination of Hydrazine

Abstract: β‐cyclodextrin (β‐CD) functionalized silver nanoparticles (AgNPs) and reduced graphene oxide (RGO) via one step electrochemical potentiodyanamic method has been prepared. Scanning electron microscopy, Energy‐Dispersive X‐ray spectroscopy, electrochemical impedance spectroscopy and cyclic voltammetry were used to study the role of β‐CD on preparation of AgNPs and RGO. RGO/β‐CD/AgNPs modified GCE showed good electrochemical activity towards electro‐oxidation of hydrazine in terms of decreasing the over potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Rejkumar et al proposed the XRD pattern of RGO/β‐CD/AgNPs. They observed only RGO and AgNPs planes are not present in β‐CD corresponding planes 51 . Whereas in our study a similar result is observed because the β‐CD has completely interacted with AgNPs as well as PVA hydrophobically.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Rejkumar et al proposed the XRD pattern of RGO/β‐CD/AgNPs. They observed only RGO and AgNPs planes are not present in β‐CD corresponding planes 51 . Whereas in our study a similar result is observed because the β‐CD has completely interacted with AgNPs as well as PVA hydrophobically.…”
Section: Resultssupporting
confidence: 87%
“…They observed only RGO and AgNPs planes are not present in β-CD corresponding planes. 51 Whereas in our study a similar result is observed because the β-CD has completely interacted with AgNPs as well as PVA hydrophobically. Overall XRD result explains that the presence of high and sharp peaks indicates good crystallinity in the AgNPs.…”
Section: Characterization Of Agnpssupporting
confidence: 86%
“…The sensitivity of our fabricated electrode was found to be 108 μA mM −1 cm −2 and the limit of detection (LOD) was calculated from the formula, LOD=3 s b /S (where, s b =standard deviation of blank signal and S=slope of the linear fit). The value of LOD was calculate to be 84 nM by substituting the value of slope of the linear fit and standard deviation of blank signal . The obtained values of linear range, sensitivity and LOD indicates that the prepared nanocomposite is a robust and an excellent electrocatalyst for the sensitive detection of DA.…”
Section: Resultsmentioning
confidence: 99%
“…The changed GCE was converted to an electrolytic solution with a pH of 5. [77] To produce AgNPs/β-CD-rGO nanocomposite, the solution was electrochemically reduced 10 times between 0 and 1.3 V. [78,79]…”
Section: Synthesis and Fabrication Of β-Cd-rgo/agnps Modified Electrodementioning
confidence: 99%